2014
DOI: 10.1108/ijchm-01-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' perspectives on service staff with disabilities in the hospitality industry

Abstract: 2014),"Measuring food and beverage service quality in spa hotels: A case study inIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…However, Gröschl (2007) suggested that travelers with disabilities may choose hotels that promote diversity over the ones that select employees to promote physical attractiveness. Kuo and Kalargyrou (2014) studied customer perceptions about being served by people with disabilities in restaurants and found that consumers demonstrated a moderately positive purchase intention for a restaurant that employs a significant amount of service staff with disabilities; however, the purchase intention varied by dining occasions. The likelihood of choosing this type of restaurant was higher in occasions with family and friends than in business or romantic occasions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gröschl (2007) suggested that travelers with disabilities may choose hotels that promote diversity over the ones that select employees to promote physical attractiveness. Kuo and Kalargyrou (2014) studied customer perceptions about being served by people with disabilities in restaurants and found that consumers demonstrated a moderately positive purchase intention for a restaurant that employs a significant amount of service staff with disabilities; however, the purchase intention varied by dining occasions. The likelihood of choosing this type of restaurant was higher in occasions with family and friends than in business or romantic occasions.…”
Section: Discussionmentioning
confidence: 99%
“…The prejudice in moralised entities and activities leads to avoidance rather than toleration (Verkuyten and Yogeeswaran, 2017). The intention to buy products of people with a health problem may demonstrate initiative of consumers with high religiosity (Kuo and Kalargyrou, 2014). A negative association between religiosity and AIDs is related stigma, which shows those who are affected by HIV/AIDs (Muturi and An, 2010):…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Corporate social strategy (CSR) can represent a potential input to differentiation strategy, and corporates can differentiate themselves effectively from rest of the competitors (Boehe and Cruz 2010). Kuo and Kalargyrou (2014) in their single-factor experimental design study found that consumers demonstrated a moderately positive purchase intention for a restaurant that employed individual with disabilities. A case study conducted in five Embrace member hotels where guests with and without disabilities shared their perception and confirmed that physical attributes of EWD did not interfere in their day to day performance, and guests reported no negative experiences (Groschl 2012).…”
Section: Resultsmentioning
confidence: 99%